Aspirin and clonidine in non-cardiac surgery: acute kidney injury substudy protocol of the Perioperative Ischaemic Evaluation (POISE) 2 randomised controlled trial. Issue 2 (25th February 2014) - Garg, Amit X; Kurz, Andrea; Sessler, Daniel I; Cuerden, Meaghan; Robinson, Andrea; Mrkobrada, Marko; Parikh, Chirag; Mizera, Richard; Jones, Philip M; Tiboni, Maria; Rodriguez, Raul Gonzalez; Popova, Ekaterina; et al.
Abstract : Introduction: Perioperative Ischaemic Evaluation-2 (POISE-2) is an international 2×2 factorial randomised controlled trial of low-dose aspirin versus placebo and low-dose clonidine versus placebo in patients who undergo non-cardiac surgery. Perioperative aspirin (and possibly clonidine) may reduce the risk of postoperative acute kidney injury (AKI). Methods and analysis: After receipt of grant funding, serial postoperative serum creatinine measurements began to be recorded in consecutive patients enrolled at substudy participating centres. With respect to the study schedule, the last of over 6500 substudy patients from 82 centres in 21 countries were randomised in December 2013. The authors will use logistic regression to estimate the adjusted OR of AKI following surgery (compared with the preoperative serum creatinine value, a postoperative increase ≥26.5 μmol/L in the 2 days following surgery or an increase of ≥50% in the 7 days following surgery) comparing each intervention to placebo, and will report the adjusted relative risk reduction. Alternate definitions of AKI will also be considered, as will the outcome of AKI in subgroups defined by the presence of preoperative chronic kidney disease and preoperative chronic aspirin use. At the time of randomisation, a subpopulation agreed to a single measurement of serum creatinine between 3 and 12 months after surgery, and the authors will examine intervention effects on this outcome. Ethics and dissemination: The authors were competitively awarded a grant from the Canadian Institutes of Health Research for this POISE-2 AKI substudy. Ethics approval was obtained for additional kidney data collection in consecutive patients enrolled at participating centres, which first began for patients enrolled after January 2011. In patients who provided consent, the remaining longer term serum creatinine data will be collected throughout 2014. The results of this study will be reported no later than 2015. Clinical Trial Registration Number: NCT01082874.